Excise Tariff Policy and Field Supervision as Instruments for Controlling the Circulation of Illegal Tobacco Products - Rina Sulistyowati; Reza Anggapratama; Moch Abdul Muiz Nur Hanip Pamungkas (Universitas Trunojoyo Madura, 2026)
The circulation of illicit tobacco products poses a serious challenge to taxation and state revenue protection. Excise tariff policies and field supervision are key instruments in controlling illicit cigarettes. This study examines how these policies and supervision practices are interpreted and implemented in controlling illicit tobacco products in Bojonegoro Regency, Indonesia, a strategic transit area in the illegal tobacco distribution network. Using a qualitative phenomenological approach, data were collected through in-depth interviews with five Customs supervisory and investigative officers and analyzed through thematic coding. Findings show that excise tariff policy is perceived not only as a fiscal instrument but also as a factor shaping illegal actors’ cost–benefit considerations, with tariff increases often followed by adaptive distribution strategies. Field supervision translates policy into enforcement risk through adaptive, intelligence-driven, and discretionary practices, including risk-based targeting and delayed interception. However, limited personnel, wide surveillance areas, and adaptive illicit networks constrain enforcement effectiveness. The study highlights that local excise control effectiveness depends on the interaction between tariff policy, field discretion, and institutional capacity, emphasizing the need to combine fiscal measures with adaptive enforcement strategies in dynamic illicit distribution areas.